(Russian) Writer‐Bloggers: Digital Perfection and the Aesthetics of Imperfection1. Issue 4 (2nd June 2014) - Rutten, Ellen
Abstract This article explores readings of (micro)blogging services as outlets for playful, "imperfect" language. Adopting a transcultural approach, it examines a blog category that has attracted scarce academic attention to date: the creative worker's blog. Through a qualitative analysis of metalinguistic statements by 14 Russian writer‐bloggers, the author tests 2 interdependent hypotheses: (H1) through metalinguistic statements and pragmatic strategies, writers present language play and "imperfect" language as prototypical for new media; and (H2) If H1 is correct, the writer‐blogger's preference for "imperfect" language caters into a broader cultural‐philosophical anxiety – one of foregrounding imperfection as an aesthetic counterresponse to digital perfection.